2017
DOI: 10.1039/c7ce01558e
|View full text |Cite
|
Sign up to set email alerts
|

Type I vs. quasi-type II modulation in CdSe@CdS tetrapods: ramifications for noble metal tipping

Abstract: We report on noble metal tipping of heterostructured nanocrystals (NCs) of CdSe@CdS tetrapods (TPs) as a chemical reaction to manifest energetic differences between type I and quasi-type II heterojunctions. The energetics between zincblende (ZB) CdSe seed and wurtzite CdS TP arms has previously been probed primarily using ultrafast spectroscopic methods. However, to interrogate the energetics of CdSe@CdS TPs from both larger and very small ZB CdSe seeds (i.e., effective diameters (Deff) 6.2 to 1.8 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 72 publications
1
32
0
Order By: Relevance
“…The results comparisons are based on the deposition sites, such as single-tip (ST), double-tip (DT), and multisite (MS) distributions. The most effective methods now tend to lower the deposition temperature, ,,,,, shorten the reaction time, , and use long alkyl amine ligands; ,, laser or lamp-assisted photodeposition may also help in obtaining more selective ST deposition. , In some cases, the hole scavenger was stated as such and identified as a short-chain alcohol (methanol, ethanol, 2-propanol, ethylene glycol), , but most of the time it is barely mentioned, and TEM images show quantum dots and DRs corrosion taking place concomitantly with the gold deposition.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results comparisons are based on the deposition sites, such as single-tip (ST), double-tip (DT), and multisite (MS) distributions. The most effective methods now tend to lower the deposition temperature, ,,,,, shorten the reaction time, , and use long alkyl amine ligands; ,, laser or lamp-assisted photodeposition may also help in obtaining more selective ST deposition. , In some cases, the hole scavenger was stated as such and identified as a short-chain alcohol (methanol, ethanol, 2-propanol, ethylene glycol), , but most of the time it is barely mentioned, and TEM images show quantum dots and DRs corrosion taking place concomitantly with the gold deposition.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction time has been mentioned to play a significant role in controlling the deposition. However, there are also results at variance: (i) Pavlopoulos et al showed that MS were obtained at short times (<30 s) and ripening took place to form ST NHDs for t > 2.5 min; (ii) O’Sullivan et al claimed that it was easy to achieve ST NHDs for t < 2 min; and (iii) Banin’s group ,, found that ST NHDs were obtained under much longer deposition times (>30 min) and at low temperature (<277 K). These different results suggest that the underlying growth mechanism remains to be investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the demand from scientists to fundamentally extend the range of shape-controlled synthesis methods and to develop unique physicochemical properties for material designs has had considerable growth concerning to the great potential of these quantum materials in the areas of nanoscience, bionanotechnology and optoelectronics. [5][6][7][8][9][10][11][12][13][14] On the other hand, ligand-induced chirality in nanostructures such as metal nanocrystals (NCs) and clusters, [15][16][17][18][19] QDs, [20][21][22][23] carbon-based materials [24][25][26] and semiconductors [27][28][29][30][31][32][33] has revolutionized the concept of basic light-matter interactions into a chiroptics realm where more sophisticated phenomena such as circular dichroism (CD) and circularly polarized luminescence (CPL) are dominant. [34][35][36] With postsynthetic ligand exchanges, the optical chirality can be transferred to the NCs via ligand-metal interactions.…”
mentioning
confidence: 99%